PENENTUAN AGROINDUSTRI BERBASIS JAGUNG TERPILIH DI PROVINSI LAMPUNG - Sri Mulyani Widyanti; Hanung Ismono; Sri Hidayati (Jurnal Teknologi & Industri Hasil Pertanian, 2011)
Most of the corn produced in Lampung Province is utilized for feed. The farmers sell the corn seed in  a market where the price is fluctuated. So far, the  number of business people in feed industry are still low, therefore the corn itself is still not fully exploited. This study was aimed to select the proper type of agro-industry for Lampung Province which was analyzed using Hierarchy Analysis Process, specifying the location of selected agro-industries by using Exponential Comparative Method. In this research, we used the research survey, data collected includes primary data and secondary data by the method of quantitative analysis and qualitative descriptive. By using hierarchy analysis process, the proper agro-industry for Lampung province is corn flour. Then, by using exponential comparison method, the proper place for developing the corn flour industry is in East Lampung regency specifically in Sribhawono. Corn flour industry viable market assessed with consideration of market opportunities to reach 35% corn flour that is equal to 1.533 million tones. The production process is done using wet and dry production methods. Based on the calculation of costs and production capacity , the sale price of the corn flour is Rp. 5800, - per kilogram.